Altruism Reflected At Victor Hugo's Les Miserables (1862):A Psychoanalytic Study Of Literature - Rukmana, Anita Rediyati; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
This research paper is aimed to show visible image of Victor Hugo's novel which is analyzed by using psychoanalytic approach. The problem of this study is how altruism is reflected in the Les Miserables novel. The objective of the research is to analyze the novel based on psychoanalytic approach proposed by Sigmund Freud. This research paper belongs to qualitative research. Data of the research are divided into two, primary data and secondary data. The primary data source is Les Miserables novel and the secondary data is taken from other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the research shows the following conclusions. First, based on the structural analysis, it can be concluded that the author delivers moral message that a good personality is reflected through honesty and sincerity in helping others. Second, based on the psychoanalytic analysis ofthe novel, it can be infered that Victor Hugo illustrates psychological phenomenon in which the character experienced an altruism.